Drug delivery systems for local anesthetics - de Paula, Eneida (2010)
Although technological innovations in the area of drug delivery claim for varied benefits, increasing the drug therapeutic index for human clinical application is the main goal pursued. Drug delivery systems for local anesthetics (LA) have attracted researchers due to many biomedical advantages associated to their application. Formulation approaches to systemically deliver LA include the encapsulation in liposomes, complexation in cyclodextrins, association with biopolymers and others carrier systems. Topical delivery systems for LA are characteristically composed by a diversity of adjuvants (viscosity inducing agents, preservatives, permeation enhancers, emollients,...) and presentations such as semisolid (gel, creams, ointments), liquid (o/w and w/o emulsions, dispersions) and solid (patches) pharmaceutical forms. The proposed formulations aim to reduce the LA concentration used, increase its permeability and absorption, keep the LA at the target site for longer periods prolonging the anesthetic or analgesic effect and, finally, to decrease the clearance, local and systemic toxicity. This review deals with the innovations pertaining to formulations and techniques for drug delivery of topical and injectable local anesthetics, as described in recent patents. © 2010 Bentham Science Publishers Ltd.